Influence of the Computer-Aided Static Navigation Technique and Mixed Reality Technology on the Accuracy of the Orthodontic Micro-Screws Placement. An In Vitro Study - Riad Deglow, Elena; Toledano Gil, Sergio; Zubizarreta Macho, Álvaro; Bufalá Pérez, María; Rodríguez Torres, Paulina Andrea; Tzironi, Georgia; Albaladejo Martínez, Alberto; López Román, Antonio; Hernández Montero, Sofía (My University, 2021)
: To analyze the effect of a computer-aided static navigation technique and mixed reality technology on the accuracy of orthodontic micro-screw placement. Material and methods: Two hundred and seven orthodontic micro-screws were placed using either a computer-aided static navigation technique (NAV), a mixed reality device (MR), or a conventional freehand technique (FHT). Accuracy across different dental sectors was also analyzed. CBCT and intraoral scans were taken both prior to and following orthodontic micro-screw placement. The deviation angle and horizontal deviation were then analyzed; these measurements were taken at the coronal entry point and apical endpoint between the planned and performed orthodontic micro-screws. In addition, any complications resulting from micro-screw placement, such as spot perforations, were also analyzed across all dental sectors. Results: The statistical analysis showed significant differences between study groups with regard to the coronal entry-point (p < 0.001). The NAV study group showed statistically significant differences from the FHT (p < 0.001) and MR study groups (p < 0.001) at the apical end-point (p < 0.001), and the FHT group found significant differences from the angular deviations of the NAV (p < 0.001) and MR study groups deviations (p = 0.0011). Different dental sectors also differed significantly. (p < 0.001) Additionally, twelve root perforations were observed in the FHT group, while there were no root perforations in the NAV group. Conclusions: Computeraided static navigation technique enable more accurate orthodontic micro-screw placement and fewer intraoperative complications when compared with the mixed reality technology and conventional freehand techniques.
Keywords: orthodontics; micro-screws; orthodontic anchorage; mini-implants; temporary anchorage devices